Retail Business and the Freight Industry in Shanxi Province of China: an Empirical study of Interactive Relationship - Ding, Huiqiong (Journal of Economics and Behavioral Studies, 2014)
The fate of the retailing industry is related to the freight industry of a country. In order to enhance the pulling power that the retailing has to the freight industry, this research investigated the interactive relationship of retailing and freight industry in Shanxi Province of China. Using the software Eviews 5.0Â®, a Co-integration Model was proposed. Evaluation of the validity of the model, using the Stationary Test, Granger Causality Test and Error Correction, proved that the model proposed had the ability to repair itself. Using the model to explain the relationship between retailing and freight results further revealed that there is a long-term equilibrium relationship between the two variables. Furthermore, this study proved that in order to enhance the pulling power that retailing has to freight industry, there is a need to pay attention to the final consumption, to support retailing and to speed up the urbanization construction.